1999
DOI: 10.1037/0022-3514.77.3.630
|View full text |Cite
|
Sign up to set email alerts
|

Expressive writing and the role of alexythimia as a dispositional deficit in self-disclosure and psychological health.

Abstract: Psychology students were randomly assigned to a condition in which they had to write for 20 min on 3 days or for 3 min on 1 day a factual description of disclosed traumas, undisclosed traumas, or recent social events. In the case of undisclosed traumatic events, intensive writing about these events showed a beneficial effect on affect and on the affective impact of remembering the event and appraisal. Participants who wrote briefly about an undisclosed traumatic event showed a more negative appraisal. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 21 publications
5
101
1
3
Order By: Relevance
“…With the exception of expression of emotional intimacy, the expressive writing intervention also produced roughly equivalent results for high versus low restrictive emotionality men. These results stand in contrast to previous expressive writing studies (e.g., Paez et al, 1999;Solano et al, 2003) indicating that individuals who have difficulty being emotionally open benefit more from expressive writing. The reliance on self-report measures might have hampered the detection of interaction effects.…”
Section: Interaction Effects Relating To Restrictive Emotionality Andcontrasting
confidence: 55%
See 3 more Smart Citations
“…With the exception of expression of emotional intimacy, the expressive writing intervention also produced roughly equivalent results for high versus low restrictive emotionality men. These results stand in contrast to previous expressive writing studies (e.g., Paez et al, 1999;Solano et al, 2003) indicating that individuals who have difficulty being emotionally open benefit more from expressive writing. The reliance on self-report measures might have hampered the detection of interaction effects.…”
Section: Interaction Effects Relating To Restrictive Emotionality Andcontrasting
confidence: 55%
“…In discussing the interaction effects, the authors argued that highly alexithymic patients derived greater benefits because expressive writing might have activated previously unavailable emotional resources in them. In another study (Paez et al, 1999), participants with higher scores on the Difficulty Describing Feelings subscale of the Toronto Alexithymia Scale (Bagby et al, 1994) and who wrote about traumatic experiences reported significantly less negative affect two months after the writing intervention compared to the control group, whereas this pattern was not repeated for those with less self-reported difficulty describing feelings. The Paez et al (1999) study is particularly relevant to the present study because in a recent analysis of men's emotional inexpressiveness, men's difficulty describing feelings was found to be strongly related to men's restrictive emotionality (Wong et al, 2006).…”
Section: Potential Benefits Of Expressive Writing For Emotionally Resmentioning
confidence: 93%
See 2 more Smart Citations
“…One found that greater alexithymia (TAS-20 total), and specifically the difficulty describing feelings facet, predicted less postsurgical distress and quicker hospital discharge among patients undergoing bladder papilloma resection who wrote about their feelings of being in the hospital (Solano, Donati, Pecci, Persichetti, & Colaci, 2003). The other study examined only this same TAS-20 facet, difficulty describing feelings, which predicted better affect at follow-up among disclosure writers (Paez, Velasco, & Gonzalez, 1999). In our view, these two studies probably found that the facet of difficulty describing feelings, which is related to inhibition and shame, predicted better outcomes following disclosure.…”
Section: Does Alexithymia Influence Treatment Process and Outcomes?mentioning
confidence: 99%